2011
DOI: 10.1016/j.ins.2010.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of a certificateless signcryption scheme in the standard model

Abstract: a b s t r a c tCertificateless signcryption is a useful primitive which simultaneously provides the functionalities of certificateless encryption and certificateless signature. Recently, Liu et al.[15] proposed a new certificateless signcryption scheme, and claimed that their scheme is provably secure without random oracles in a strengthened security model, where the malicious-but-passive KGC attack is considered. Unfortunately, by giving concrete attacks, we indicate that Liu et al. certificateless signcrypti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Liu [17] in 2010 proposed a certificateless signcryption scheme in the standard model where he gives proof of his scheme being efficient and practical. How-ever, in 2011 J. Weng [18] proved that the scheme pro-posed by Liu et al is insecure under type-2 adversary at-tacks. Thereafter efforts were taken by many researchers to address the above issue but it did not proved to be successful.…”
Section: Certificateless Signcryption Schemes With Bilinear Pairingmentioning
confidence: 99%
“…Liu [17] in 2010 proposed a certificateless signcryption scheme in the standard model where he gives proof of his scheme being efficient and practical. How-ever, in 2011 J. Weng [18] proved that the scheme pro-posed by Liu et al is insecure under type-2 adversary at-tacks. Thereafter efforts were taken by many researchers to address the above issue but it did not proved to be successful.…”
Section: Certificateless Signcryption Schemes With Bilinear Pairingmentioning
confidence: 99%
“…In 2010, Liu et al [18] proposed certificateless signcryption as an extension of ID-based signcryption. Unfortunately, Weng et al [19] showed that Liu et al's scheme is neither semantically secure against chosen ciphertext attacks nor existentially unforgeable against chosen message attacks.…”
Section: Introductionmentioning
confidence: 99%
“…The scheme proposed by Yap et al [21] was shown insecure and modified by Li et al [13]. The design and analysis of Certificateless threshold signature schemes and certificateless signcryption schemes have also been studied in [5,22,14,17] respectively. In CL-PKC, a malicious-but-passive KGC [3] may be dishonest from the start of the system setup.…”
Section: Introductionmentioning
confidence: 99%